In house electrostatic field meter calibration for improved ESD protection / Husna Abdul Rahim - Husna, Abdul Rahim (2019)
This research project presented an improved in house calibration procedure for electrostatic field meter. The proposed improved arrangement is by using copper parallel plates with the optimum separation distance of 6.01 mm between plates. The material properties test, repeatability test and reproducibility test have been conducted throughout the project. The material properties test shows that copper is the suitable material to be used as the calibration plate due to its behaviour that can withstand high voltage up to 8 kV. The repeatability test conducted shows that the arrangement produces consistent results in five cycles of measurements. As for the reproducibility test where taken into account that the arrangement has been dismantled before undergoes the reproducibility test shows that the arrangement is reproducible. This study is conducted for the improvement electrostatic discharge (ESD) protection monitoring in the production line. ESD protection can prevent from any hazard caused by ESD. Calibration of the electrostatic meter is required for the confidence in its measuring accuracy.